Molecular assessment of extended-spectrum beta lactamases among gram-negative bacilli bacteria causing community acquired urinary tract infection among females in Southwestern Nigeria. (2021)
Background: Urinary tract infections (UTI) is commoner in females than males and mainly caused by Gram Negative bacilli. The emergence of Extended – spectrum beta lactamases (ESBL) has made its treatment difficult especially in the community because of limited therapeutic options. This study was undertaken to determine the prevalence of ESBL-producing Gram negative bacilli causing UTI among females in Babcock University Community; evaluate the associated risk factors and to determine the prevalence of the associated genes among the ESBL isolates. Methods: A descriptive cross-sectional study of which 200 female participants with clinical UTI were recruited in Babcock University Community. Pretested interviewer–based structured questionnaire was used to obtain the socio demographic and risk factors. Mid-stream urine was also collected for evaluation of ESBL- producing Gram-negative bacilli. DNA extraction was done for ESBL positive isolates and SHV, TEM, CTX-M and OXA ESBL genes were detected by PCR. SPSS Version 23.0 was used for data analysis. Results: The 200-urine samples tested from the participants yielded 33-Gram negative bacilli isolates. Out of these 33 isolates, 17(51.5%) were ESBL-producers giving prevalence rate of 8.5% among the participants. The distribution of the ESBL genes among the ESBL isolates was as follows: SHV 15/17(88.2%), TEM 4/17(23.5%), CTX-M 3/17(17.6%) and OXA 5/17(29.4%). No associated risk factors were found. Conclusion: All the four types of ESBLgenes evaluated were present among the participants. Routine screening for ESBL for Community acquired UTI is necessary to curb treatment failure.